Anti-phosphatidylserine antibody levels are low in multigravid pregnant women in a malaria-endemic area in Nigeria, and do not correlate with anti-VAR2CSA antibodies - Fasanya, Adebimpe; Mohammed, Nurat; Saleh, Bandar Hasan; Tijani, Muyideen Kolapo; Teleka, Alexandra; Quintana, Maria del Pilar; Hviid, Lars; Persson, Kristina E. M. (Frontiers in Cellular and Infection Microbiology, 2023)
Anemia is a common malaria-associated complication in pregnant women in endemic regions. Phosphatidylserine (PS) is exposed to the immune system during the massive destruction of red blood cells (RBCs) that accompany malaria, and antibodies against PS have been linked to anemia through destruction of uninfected RBCs. We determined levels of anti-PS IgG antibodies in pregnant women in Ibadan, Nigeria and correlated them to parameters of importance in development of anemia and immunity. Anti-PS correlated inversely with Packed Cell Volume (PCV), indicating that the antibodies could contribute to anemia. There was no correlation with anti-VAR2CSA IgG, haptoglobin or parasitemia, indicating that the modulation of anti-PS response is multifactorial in nature. Anti-PS levels were lowest in multigravidae compared to both primigravidae and secundigravidae and correlated inversely with age. In conclusion, lower levels of anti-PS in multigravidae could be beneficial in avoiding anemia.